Depressive symptomatology and negative automatic thoughts among Malays and Chinese adolescents in Malaysia - Saliza binti Karia @ Zakaria (Kulliyyah of Islamic Revealed Knowledge and Human Scieences, International Islamic University Malaysia, 1999)
This study explores depressive symptomatology and various dimensions of negative automatic thoughts among two groups of adolescents, the Malays and the Chinese in Malaysia. The objective of the study is to find out whether cultureal dictates or ethnic identity of the subjects influences depression and automatic thoughts. A pilot-study was conducted to adapt two scales namely, the Reynolds Adolescent Depression Scale (RADS) and the AutomaticThoughts Questionnaire (ATQ) which have been translated into the Malay language. A sample of 120 subjects within the age range of 16-18 years was selected. They consisted of 31 male and 25 female Malays, and 37 male and 27 female Chinese. The scales were translated into Malay following the translation and back-translation procedure. The internal consistency reliability of RADS was 0.74, while that of ATQ was 0.86. A main study was conducted to examine depressive sympptomatology and automatic thoughts among Malay and Chinese adolescents. The scales adapted in the pilot-study were used. Three hundred and fifty two subjects, including 169 Malays and 183 Chinese, from three secondary schools in Kedah participated in the study. A total of 70 male and 99 female Malays, and 73 male and 99 female Chinese subjects were obtained. The age of the subjects ranged from 16-18 years. The main result showed that the Malays were significantly more depressed than the Chinese. Malays also scored higher on negative automatic thoughts although the difference was not significant. The internal consistency reliability of RADS was 0.79, while that of ATQ was 0.91. No statistically significant gender differences were found on both scales.